Efektivitas E-Court dalam Penyelesaian Sengketa Ekonomi Syariah di Pengadilan Agama Surakarta - Ryan Alan Firnanda; Nur Rosidah, Zaidah (Jurnal Supremasi, 2024)
E-Court as an electronic justice system formed based on Supreme Court Regulation Number 3 of 2018 (PERMA 3/2018) jo PERMA 1 of 2019, regulates e-filling (registration), e-payment (payment), e-summons (summons), and e-litigation (trial). The application of digitalization breakthroughs and innovations to the justice system in Indonesia is urgent to know its effectiveness, especially in the aspect of sharia economic dispute resolution, considering Indonesia as the largest Muslim country in the world. Through empirical legal research at the Surakarta Religious Court, it is known that the implementation of e-court in sharia economic dispute resolution at the Surakarta Religious Court has not been optimally accepted by the litigants, and still has many obstacles that must be corrected.